A Nonlinear Concurrent Butterfly Equalizer - Mayer, Kayol Soares; Soares, Jonathan Aguiar; Arantes, Dalton Soares (Společnost pro radioelektronické inženýrství, 2021)
Optical communication systems operating with high data rates and dual-polarization are frequently disrupted by chromatic and polarization mode dispersions. Fixed filters usually mitigate chromatic dispersion; on the other hand, polarization mode dispersion (PMD), due to its stochastic behavior, is reduced by adaptive filters, such as channel equalizers. In this context, this article proposes a novel blind equalization architecture, based on the nonlinear modified concurrent equalizer (NMCE) expanded to a butterfly structure. The proposed nonlinear concurrent butterfly equalizer (NCBE) combines the reduced uncertainty and the sharper decision regions of the NMCE in both X and Y polarizations, resulting in improved performance. The NCBE is compared with the constant modulus algorithm (CMA), the modified CMA (MCMA), and the concurrent CMA-SDD (soft direct decision), all of them in butterfly architectures and with fractionally-spaced equalization. Results show that the proposed solution presents a reduced bit error rate (BER) and steady-state mean squared error (MSE) figures compared with the CMA, MCMA, and CMA-SDD equalizers the NCBE cross-shaped noise of the nonlinear equalizer output. Also, the NCBE can operate at higher values of PMD compared to the least mean square (LMS) equalizer without the necessity of delaying polarization X, Y, or both.
Keywords: Data center interconnect; equalization architecture; blind equalizers; polarization mode dispersion